2013
DOI: 10.1002/bmc.2996
|View full text |Cite
|
Sign up to set email alerts
|

Utility of noninvasive biomatrices in pharmacokinetic studies

Abstract: Blood and plasma are the biomatrices traditionally used for drug monitoring and their pharmacokinetic profiling. Blood is the circulating fluid in contact with all organs and tissues of body and thus is the most representative fluid for measuring systemic drug levels. However, venipuncture suffers from the caveat of being an invasive technique which often makes people reluctant to participate in clinical studies. Thus, there is a need for noninvasive bio-fluids that are ethically appropriate, cost-efficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 144 publications
0
45
0
Order By: Relevance
“…Nursing mothers can be exposed to medications or other therapeutics, either short or long-term, depending on the need of the treatment [1].…”
Section: Pharmaceutical Contaminantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nursing mothers can be exposed to medications or other therapeutics, either short or long-term, depending on the need of the treatment [1].…”
Section: Pharmaceutical Contaminantsmentioning
confidence: 99%
“…Its application to human milk samples is, however, limited, as it does not fully remove the lipids and the oligosaccharides (HMO) present in this matrix [1,5,22,23].…”
Section: Pharmaceutical Contaminantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apocrine and apoeccrine sweat glands located in the axillary and genital regions of the body have a distinct secretory mechanism from eccrine sweat glands, and apocrine and apoeccrine sweat are less well characterized compared to eccrine sweat. Therefore, (eccrine) sweat might offer access to a potentially valuable and noninvasive biological sample that could help improve subject compliance in pharmacokinetic and biomedical studies, as has been demonstrated with other non-invasive matrices such as hair, saliva and tears (11). …”
Section: Introductionmentioning
confidence: 99%